Impact of gestational diabetes diagnosis on concurrent depression in pregnancy. (3rd July 2021) - Miller, Nathaniel E.; Curry, Elizabeth; Laabs, Susan B.; Manhas, Manisha; Angstman, Kurt
Abstract: Background: Gestational diabetes mellitus (GDM) affects nearly 5% of US pregnancies and is associated with poor outcomes. Perinatal depression is also associated with substantial risks to both the fetus and mother. There is limited data about the relationship between GDM and antenatal depression. Therefore, we looked at whether a GDM diagnosis would be associated with an increased risk of depression during pregnancy. Methods: We studied 562 pregnant women from 1 July 2013 to 30 June 2015, in a prospective multi-part survey on clinical obstetrical outcomes. Results: Of the 562 patients, 46 patients (8.0%) were diagnosed with GDM. There was no statistical difference between the groups for either history of prior or post-partum depression. Diagnosis of depression was present in 15.2% of the GDM group but only 6.2% of the control group. Regression modeling demonstrated an adjusted odds ratio (AOR) of 2.46 for a diagnosis of depression when the patient had a diagnosis of GDM (95% CI 1.01–6.03, p =.049). Conclusions: The diagnosis of GDM was associated with an elevated risk of concomitant pregnancy diagnosis of depression. Given the elevated risk to patients diagnosed with GDM, a more frequent depression screening interval could be considered during the remainder of the pregnancy, such as each prenatal visit.